Greek Libraries Network Purpose goals vision. The audience development in libraries through educational programs for children - Mini, Pamela (Journal of Integrated Information Management, 2019)
Purpose - In 2015 the National Library of Greece took over the Greek Libraries Network to support the efforts of academic, research, public, municipal and school libraries in the country to develop and advance the services they offer to the public. The main objective is to make this network a center of knowledge diffusion, networking and professional communication among its members as well as making libraries hubs of creativity for everyone. Design/methodology/approach - The existence of this network gives each member-library the ability to multiply its users, since the users of each library are members of the entire network. The actions of the Greek Libraries Network aim at audience development in the libraries, with a special focus on children, in order to create a new generation of readers. Findings - The proposed educational programs promote reading through specific themes and books. Through specially designed workshops children can experience the library as a space that offers innumerable opportunities for education and creativity. Originality/value - In this endeavor, the National Library of Greece stands shoulder to shoulder by visiting the natural spaces of each member-library of the Greek Libraries Network, heeding their needs and concerns, but also getting feedback and new ideas for the improvement of its services.